Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/glycob/cwy044
|View full text |Cite
|
Sign up to set email alerts
|

Quiescin sulfhydryl oxidase 1 (QSOX1) glycosite mutation perturbs secretion but not Golgi localization

Abstract: Quiescin sulfhydryl oxidase 1 (QSOX1) catalyzes the formation of disulfide bonds in protein substrates. Unlike other enzymes with related activities, which are commonly found in the endoplasmic reticulum, QSOX1 is localized to the Golgi apparatus or secreted. QSOX1 is upregulated in quiescent fibroblast cells and secreted into the extracellular environment, where it contributes to extracellular matrix assembly. QSOX1 is also upregulated in adenocarcinomas, though the extent to which it is secreted in this cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The remaining supernatant was passed through a 0.45 µ m filter, and protein was purified by Ni‐NTA chromatography. The catalytic region of human QSOX1 was purified in a similar manner using an expression vector previously described [ 38 ]. Escherichia coli Trx was purified from bacteria essentially as described except without detergent [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The remaining supernatant was passed through a 0.45 µ m filter, and protein was purified by Ni‐NTA chromatography. The catalytic region of human QSOX1 was purified in a similar manner using an expression vector previously described [ 38 ]. Escherichia coli Trx was purified from bacteria essentially as described except without detergent [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…1d, i). Although it remains unclear how the disulfides in the D′D3 dimer interface would reshuffle or form at ~pH 5.8 in Golgi and various mechanisms have been proposed 7,9 , our cryo-EM structure of a D′D3 dimer complexed with D1D2s shows that the two Cys 1097 are largely buried in the center of the dimeric interface and there is limited space to allow the participation of any bulky redox-regulating enzymes (Supplementary Figs. S7, S8).…”
mentioning
confidence: 97%
“…QSOX2 also shares 50 % similarity with QSOX1, which is more studied and has recently been identified as a marker of metastasis in several cancers, including prostate (81, 82), pancreatic (36, 83), and breast (84, 85) cancers. QSOX1 localizes to the ER and Golgi but can be secreted (83, 8688), in a mechanism that requires its N-linked glycan (89). Here we have demonstrated that QSOX2 carries polySia on both N - and O -linked glycans, and that secreted QSOX2 is polysialylated.…”
Section: Discussionmentioning
confidence: 99%